Synthesis and acetylcholinesterase/butyrylcholinesterase inhibition activity of new tacrine-like analogues - Marco, JL (2015)
The synthesis and preliminary results for acetylcholinesterase and butyrylcholinesterase inhibition activity of a series of pyrano[2,3-b]quinolines (2, 3) and benzonaphthyridines (5, 6) derivatives are described. These molecules are tacrine-like analogues which have been prepared from readily available polyfunctionalized ethyl [6-amino-5-cyano-4H-pyrans and 6-amino-5-cyanopyridine s]-3-carboxylates via Friedlander condensation with selected ketone s. These compounds showed moderate acetylcholinesterase inhibition activity, the more potent (2e, 5b) being 6 times less active than tacrine. The butyrylcholinesterase activity of some of these molecules is also discussed. (C) 2001 Elsevier Science Ltd. All rights reserved.